2021
DOI: 10.1002/mds.28783
|View full text |Cite
|
Sign up to set email alerts
|

Blood Neurofilament Light Chain in Genetic Ataxia: A Meta‐Analysis

Abstract: A BS TRACT: Background: No comprehensive metaanalysis has ever been performed to assess the value of neurofilament light chain (NfL) as a biomarker in genetic ataxia.Objective: We conducted a meta-analysis to summarize NfL concentration and evaluate its utility as a biomarker in genetic ataxia. Methods: Studies were included if they reported NfL concentration of genetic ataxia. We used log (mean AE SD) NfL to describe mean raw value of NfL. The effect size of NfL between genetic ataxia and healthy controls (HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(36 citation statements)
references
References 54 publications
1
35
0
Order By: Relevance
“…There have been 33 meta‐analyses on the wealth of data on Nf as a biomarker for neurodegeneration over the past 15 years (Agah et al, 2018; Alagaratnam, Widekind, et al, 2021; Angelopoulou et al, 2021; Arneth & Kraus, 2022; Cai & Huang, 2018; Choong et al, 2019; Cong et al, 2021; Forgrave et al, 2019; Gao et al, 2020b; Ge et al, 2018; Hoiland et al, 2022; Hu et al, 2017; Jin et al, 2019; Karantali, Kazis, Chatzikonstantinou, et al, 2021; Karantali, Kazis, McKenna, et al, 2021; Katayama et al, 2020; Koychev et al, 2021; Li et al, 2016; Liu et al, 2022; Liu, Chen, et al, 2020; Martin et al, 2019; Mondello et al, 2021; Peng et al, 2022; Petzold et al, 2007; Rübsamen et al, 2022; Sako et al, 2015; Sferruzza et al, 2021; Wang et al, 2019; Wang et al, 2020a; Wang et al, 2020b; Xu et al, 2016; Zhang et al, 2022; Zhao et al, 2019; Zhou et al, 2021).…”
Section: Meta‐analysesmentioning
confidence: 99%
“…There have been 33 meta‐analyses on the wealth of data on Nf as a biomarker for neurodegeneration over the past 15 years (Agah et al, 2018; Alagaratnam, Widekind, et al, 2021; Angelopoulou et al, 2021; Arneth & Kraus, 2022; Cai & Huang, 2018; Choong et al, 2019; Cong et al, 2021; Forgrave et al, 2019; Gao et al, 2020b; Ge et al, 2018; Hoiland et al, 2022; Hu et al, 2017; Jin et al, 2019; Karantali, Kazis, Chatzikonstantinou, et al, 2021; Karantali, Kazis, McKenna, et al, 2021; Katayama et al, 2020; Koychev et al, 2021; Li et al, 2016; Liu et al, 2022; Liu, Chen, et al, 2020; Martin et al, 2019; Mondello et al, 2021; Peng et al, 2022; Petzold et al, 2007; Rübsamen et al, 2022; Sako et al, 2015; Sferruzza et al, 2021; Wang et al, 2019; Wang et al, 2020a; Wang et al, 2020b; Xu et al, 2016; Zhang et al, 2022; Zhao et al, 2019; Zhou et al, 2021).…”
Section: Meta‐analysesmentioning
confidence: 99%
“…The degeneration of neurons is believed to lead to an increase in the levels of NFL in patient biofluids, making it a useful biomarker for neurodegenerative diseases ( Gaiottino et al, 2013 ; Zeitlberger et al, 2018 ; Siller et al, 2019 ; Weishaupl et al, 2019 ). In SCA3, we and others have observed that NFL levels in the plasma and CSF can distinguish patients from controls ( Li et al, 2019 ; Peng et al, 2020 ; Prudencio et al, 2020 ; Wilke et al, 2020 ; Peng et al, 2021 ), and some studies have detected a significant correlation between serum NFL levels and disease severity ( Li et al, 2019 ; Peng et al, 2020 ; Wilke et al, 2020 ). Levels are also increased in asymptomatic expanded ATXN3 carriers compared to healthy controls and may further increase as patients near their anticipated age of onset ( Peng et al, 2020 ; Prudencio et al, 2020 ; Wilke et al, 2020 ; Peng et al, 2021 ).…”
Section: Resultsmentioning
confidence: 87%
“…In SCA3, we and others have observed that NFL levels in the plasma and CSF can distinguish patients from controls ( Li et al, 2019 ; Peng et al, 2020 ; Prudencio et al, 2020 ; Wilke et al, 2020 ; Peng et al, 2021 ), and some studies have detected a significant correlation between serum NFL levels and disease severity ( Li et al, 2019 ; Peng et al, 2020 ; Wilke et al, 2020 ). Levels are also increased in asymptomatic expanded ATXN3 carriers compared to healthy controls and may further increase as patients near their anticipated age of onset ( Peng et al, 2020 ; Prudencio et al, 2020 ; Wilke et al, 2020 ; Peng et al, 2021 ). In our mice, we found that NFL was increased in the CSF of Q84 mice compared to Q28 controls ( Figure 2H ).…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations